SOCIALIZATION OF INFORMED CONSENT FORM DESIGN AT JIMMY MEDIKA MOTHER AND CHILD HOSPITAL BORNEO (Jurnal Abdimas Administrasi Kesehatan, 2022)
Informed consent is a form in the form of medical action consent given by the patient or his closest family after obtaining a complete explanation of the medical action to be performed on the patient. The redesign of the informed consent form is a redesign to include the old guidelines for the creation, control, design and determination to be implemented by health workers and health administration employees at Jimmy Medika Borneo Mother and Child Hospital. The community service activity of the ITKES Wiyata Husada Samarinda health administration undergraduate study program which was carried out at the Jimmy Medika Borneo Mother and Child Hospital aimed to provide understanding in the context of redesigning conventional informed consent forms using paper to be digital-based. This activity was initiated by providing material on the benefits of redesigning digital-based informed consent forms. These activities are based on initial research and then followed up again in community service activities. The activity ended with an evaluation by distributing a questionnaire form through google form. The result of this community service activity is that there is extraordinary success and achievement for partners and institutions of ITKES Wiyata Husada Samarinda in mutual benefit.